Competing endogenous RNA (ceRNA) networks in Parkinson's disease: A systematic review - Asadi, Mohammad Reza; Abed, Samin; Kouchakali, Ghazal; Fattahi, Fateme; Sabaie, Hani; Moslehian, Marziyeh Sadat; Sharifi-Bonab, Mirmohsen; Hussen, Bashdar Mahmud; Taheri, Mohammad; Ghafouri-Fard, Soudeh; Rezazadeh, Maryam (Frontiers in Cellular Neuroscience, 2023)
Parkinson's disease (PD) is a distinctive clinical syndrome with several causes and clinical manifestations. Aside from an infectious cause, PD is a rapidly developing neurological disorder with a global rise in frequency. Notably, improved knowledge of molecular pathways and developing novel diagnostic methods may result in better therapy for PD patients. In this regard, the number of research on ceRNA axes is rising, highlighting the importance of these axes in PD. CeRNAs are transcripts that cross-regulate one another via competition for shared microRNAs (miRNAs). These transcripts may be either coding RNAs (mRNAs) or non-coding RNAs (ncRNAs). This research used a systematic review to assess validated loops of ceRNA in PD. The Prisma guideline was used to conduct this systematic review, which entailed systematically examining the articles of seven databases. Out of 309 entries, forty articles met all criteria for inclusion and were summarized in the appropriate table. CeRNA axes have been described via one of the axes' shared key components, which includes lncRNAs like NEAT1, SNHG family, HOTAIR, MALAT1, XIST, circRNAs, and lincRNAs. Understanding the multiple aspects of this regulatory structure may aid in elucidating the unknown causal causes of PD and providing innovative molecular therapeutic targets and medical fields.